Global Trends in Public Sector Human Resource Management: A Bibliometric Analysis - Muslim Afandi; Syed Agung Afandi; Rizki Erdayani (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2026)
This study establishes a comprehensive science mapping blueprint of global public sector human resource management (HRM) scholarship from 2000 to 2024, shifting administrative reform discourse toward a multi-layered structural diagnostic. Employing a tri-dimensional bibliometric network analysis within the VOSviewer environment, this research systematically evaluates the intellectual landscape through three distinct analytical lenses: structural network density, temporal emergence trends, and thematic evolutionary mapping. The empirical findings expose a deeply consolidated institutional core focused on traditional public administration rules, bureaucratic enforcement, and classic employee behavioral outcomes. Concurrently, evolutionary mapping tracks a severe conceptual polarization, revealing that the emerging technological cluster comprising HR analytics, digital transformation, and data-driven systems remains structurally isolated on the periphery, far removed from foundational merit systems and public accountability frameworks. To bridge these systemic frictions, this study provides a crucial policy recommendation: central personnel agencies must move past fragmented technological acquisitions and actively mandate integrated administrative regulations that legally harmonize data-driven algorithmic automation with public sector ethics, representative bureaucracy, and civil service statutory protections. This structural realignment is essential for ensuring that digital public management innovations do not compromise institutional state capacity or democratic accountability.